Effectiveness of E-BLUD Implementation, HR Competence on Quality, Timeliness, and Audit Opinion of Financial Reports - Drajad Mulyani; Susilaningtyas B Kurniawati; Supartini Supartini (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This study aims to analyze the effectiveness of the implementation of the E-BLUD system and human resource (HR) competencies on the quality, timeliness, and audit opinions of financial statements at the Tawangmangu Health Center. The problem raised is the obstacle in the use of E-BLUD caused by the low understanding of human resources and its influence on the performance of financial statements. The research method used is qualitative with a case study approach through in-depth interviews, participatory observation, and document analysis. The results of the study show that the implementation of E-BLUD increases efficiency and effectiveness in the preparation of financial statements, accelerates the reporting process, and supports the achievement of positive audit opinions. However, obstacles in the form of limited digital competencies of human resources and incompatibility of educational backgrounds are still obstacles in optimizing the use of the system. These findings affirm the importance of improving human resource competencies through regular training and management support to optimize the benefits of E-BLUD. In conclusion, the effectiveness of E-BLUD and HR competencies have a significant effect on improving the quality, timeliness, and achievement of better audit opinions of financial statements, but full success requires continuous investment in human resource capacity development.